Peran Fintech Dalam Upaya Untuk Meningkatkan Literasi Keuangan Pada Masyarakat di Jakarta - Siti Ruhana Dara; Mariah Mariah (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2020)
This study aims to analyze the effect of fintech as measure by the TAM measurment model, with perceive usefulness and perceive ease of use with financial literacy for dependent variable. The research consist of 110 respondents who filled out a questioneras research data. The analysis used is multiple linear regression. The result show that perceive usefulness and perceive ease of use affect financial literacy.while partial, perceive usefulness affect financial literacy but perceive ease of use has no effect to financial literacy